Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 433: 101



Work Step by Step

We can use the FOIL method to simplify $(2x+3)(x-5)$. F=$2x\times x=2x^{2}$ O= $2x\times-5=-10x$ I=$3\times x=3x$ L=$3\times-5=-15$ Now, we can add these terms together. $2x^{2}+(-10x)+3x+(-15)=2x^{2}-7x-15$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.